STUDENT PERSPECTIVES ON JASP AS A LEARNING TOOL IN ENGLISH EDUCATIONAL STATISTICS - Abdul Syahid; Dhea Nuraisyah; Miftahul Jannah; Sumarni, Sumarni (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2025)
This study aimed to explore students' views on using JASP (Jeffreys’s Amazing Statistics Program) as a learning tool in an educational statistics course within the English Education Program. Using a quantitative approach, the study gathered data that allowed for statistical insights into students' understanding and experiences with the tool. Questionnaires were distributed to 23 students selected through convinience sampling. The results showed that many students felt JASP supported their grasp of statistical concepts, helped them better interpret data, and reduced the likelihood of errors in their analyses. However, some students expressed a need for more guidance and practice to fully benefit from the tool. Overall, while JASP showed promise in enhancing statistical learning, its effective use would benefit from structured support to help students make the most of it in their studies.